Fourier Transform Infrared FT-IR Spectoroscopic Analysis of Spirulina - Pugazhendy, K (International Journal of Pharmaceutical & Biological Archive, 2012)
Fourier Transform Infrared FT-IR Spectoroscopic Analysis of Spirulina